2012
DOI: 10.1038/pr.2012.173
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipid levels and body weight altered by intrauterine growth restriction and postnatal fructose diet in adult rats

Abstract: Background: Intrauterine growth restriction (IUGR) is known to affect the risk of adult diseases. consumption of lipogenic fructose is increasing, and it is used as an enhancer of metabolic syndrome in rat experiments. The effects of IUGR, postnatal fructose diet, and their interaction on the lipid profile and adiposity were studied in adult rats. Methods: IUGR was induced by providing pregnant rats with 50% of daily food intake. From 1 mo onward, half of the offspring received a fructose-rich diet and were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
5
15
0
Order By: Relevance
“…15,138,139 Following reduced in utero fetal growth, through global feed restriction, a postnatal high (60%)-fructose diet, from 1 month of age, evoked hypertriglyceridaemia and hyperinsulinaemia in both the sexes and decreased fasting glucose levels in female rats at 6 months of age. 140 Further, the postnatal fructose diet resulted in an increased lipid content percentage in the retroperitoneal and intra-abdominal adipose tissues in male rats. 140 In addition, fetal protein deprivation, as a means of inducing an adverse in utero environment, has been studied extensively in a number of animal models and results in metabolic changes later in life, often the result of epigenetic changes and insulin resistance phenotypes.…”
Section: Effects Of Fructose On Fetal and Offspring Physiologymentioning
confidence: 98%
See 2 more Smart Citations
“…15,138,139 Following reduced in utero fetal growth, through global feed restriction, a postnatal high (60%)-fructose diet, from 1 month of age, evoked hypertriglyceridaemia and hyperinsulinaemia in both the sexes and decreased fasting glucose levels in female rats at 6 months of age. 140 Further, the postnatal fructose diet resulted in an increased lipid content percentage in the retroperitoneal and intra-abdominal adipose tissues in male rats. 140 In addition, fetal protein deprivation, as a means of inducing an adverse in utero environment, has been studied extensively in a number of animal models and results in metabolic changes later in life, often the result of epigenetic changes and insulin resistance phenotypes.…”
Section: Effects Of Fructose On Fetal and Offspring Physiologymentioning
confidence: 98%
“…140 Further, the postnatal fructose diet resulted in an increased lipid content percentage in the retroperitoneal and intra-abdominal adipose tissues in male rats. 140 In addition, fetal protein deprivation, as a means of inducing an adverse in utero environment, has been studied extensively in a number of animal models and results in metabolic changes later in life, often the result of epigenetic changes and insulin resistance phenotypes. 141,142 Furthermore, changes in the mRNA expression of some key hepatic gluconeogenic and glycolytic enzymes, such as fructose-1,6-bisphosphatase and pyruvate kinase, have been reported following a low-protein exposure in utero.…”
Section: Effects Of Fructose On Fetal and Offspring Physiologymentioning
confidence: 98%
See 1 more Smart Citation
“…Studies from other groups also demonstrate a variety of sex-divergent responses in IUGR. Malo et al, for example, reported that IUGR females fed a fructose-rich diet maintained a milder phenotype with maintained insulin sensitivity and lower adipose tissue lipid content in comparison to IUGR males on the same diet [32]. Studies on hypertension have also reported that IUGR female animals do not develop as severe features of high blood pressure and vascular dysfunction as males [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in fetal development and growth have been associated with lifelong adverse health problems (48). Intrauterine growth restriction increases low-density lipoprotein cholesterol in rats and the fructose diet which is used as an enhancer of metabolic syndrome causes hypertriglyceridemia and hyperinsulinemia and decreased fasting glucose levels in rats (49). In rats maternal fructose intake during pregnancy causes maternal hyperglycemia and up-regulates hepatic sterol regulatory element-binding protein-1c expression in fetuses and in dams; leading to defects in carbohydrate and lipid metabolism in the adult offspring (50).…”
Section: Fetal Protein Metabolismmentioning
confidence: 99%